Narrative development in a multilingual context - Verhoeven, Ludo Th; Strömqvist, Sven, 1954- (Studies in bilingualism, 2001)
In this volume, the results of a number of empirical studies of the development of narrative construction within a multilingual context are presented and discussed. It is explored what operating principles underlie the process of narrative production in L1 and L2. Developmental relations between form and function will be studied across a broad range of functional categories, such as temporality, perspective, connectivity, and narrative coherence. Moreover, a variety of language contact situations is considered with broad variation in the typological distances between the languages in order to.